ISLAMIC POLITICAL DISCOURSE ON NONMUSLIM LEADERSHIP IN THE MUSLIM STATE - Ibnu Syarif, H. Mujar (Jurnal Syariah, 2009)
This article intends to discuss critical opinions of Muslims political experts, about the possibility of a non-Muslim to be a president in a Muslim State. Until recently, the classical Islamic discourses on this issue tend to be trapped in the normative analysis model that seems intolerant and rigid. These discourses to some extent do not appreciate the social, cultural, historical and political complexities of the Muslim community. Hence, the classical discourses have been viewed by many contemporary scholars failed to respond to the present social-political dynamic especially from multiculturalism and democracy perspective. This article attempts to trace the forgotten and rarely discussed dimensions. This study used the library research and interview approach. The library research was conducted by gathering data from sources of bibliography related to the topic. This article managed to yield the following conclusions. Based on the stipulations in the al-Qur'an and al-Sunnah on non-Muslim leadership, the majority of authoritative ulemas (scholars) are firmed with their opinion whereby under normal circumstances, Muslims residing in Muslim state are prohibited to choose a non-Muslim president. However, under certain unforeseen circumstances, for example when Muslims are under political pressure, they are allowed to choose a non-Muslim president. Nevertheless, there are still a handful of liberal Muslim intellectuals who do not possess Shariah background; have adverse opinion. Muslims in a Muslim country are allowed to choose a non-Muslim president under any circumstances simply because the stipulations in al-Qur'an and al-Sunnah that forbid Muslims to elect a non-Muslim president is no longer applicable in the present time.